Обобщенная задача упаковки и распределения мелкопартионных потоков в многопродуктовых иерархических коммуникационных сетях и ее последовательная декомпозиция - Васянин, В.А. (Екологічна безпека та природокористування, 2012)
In work the mathematical model of the generalized problem of packing and distribution a small packages of flows in whicha lot of the major factors being characteristic for processing and transfer of flows in real multicommodity hierarchical networksis taken into account is offered. Her decomposition to a set of four independent problems, which consecutive decision allows to receive circuits of formation and distribution of flows for the generalized problem is carried out.